The Effectiveness of the Team Quiz Learning Model Incorporating Wordwall in PKn Learning in Islamic Elementary Schools - Putri, Fika Nanda; Rofiq, Mohammad (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2023)
This research is motivated by the breadth of Civics material, which makes it difficult for students to think critically and creatively in Civics lessons which tends to be boring, resulting in unsatisfactory test scores. This study aims to find out how the effectiveness of the Quiz Team learning model combining Word Wall in improving student learning outcomes in class V MI AL Islam Mangun sari 01 Gunungpati. This research approach is quantitative with a pre-experimental design with a one group pretest-posttest design. This study used the entire population as a sample, namely class V which consisted of 18 students. Data that support this research are primary test data and secondary data (student data, teacher data, teaching staff data, and school conditions). Data collection techniques are carried out by observation and tests. And documentation. Data analysis techniques used the initial normality test analysis and hypothesis testing using the t-test (Paired Sample t-test) to determine its effectiveness using the N-Gain test. Based on the data obtained, namely the pretest-posttest, which has been tested on students, and the t-test results obtained, namely t-count = 39,813 with t-table = 2,042. Acceptance test criteria Ha if t-count > t-table, then the Quiz Team and word wall learning models are said to be effective in improving learning outcomes through pretest-posttest value data. The pretest average obtained is 43.88, and the posttest average is 79.66. The value of n gain indicated an increase in understanding of the concept with a value of 0.65, which was categorized as effective.